Case Study: Implementation of Occupational Health and Safety for Engineering Officers at PT. PLN (Persero) ULP Regency X - Romadhoni, Novita; Purwaningrum, Solikhati Indah (Poltekkes Kemenkes Palu, 2025)
Background: This study was conducted to determine the extent to which the implementation of the K3 program has been carried out, including aspects of work procedures, use of Personal Protective Equipment (PPE), and monitoring of work X. This case study is focused on providing a comprehensive picture of the challenges faced by PT. PLN (Persero) ULP Regency. Methods: This study uses a qualitative descriptive method with a purposive sampling technique. The population and sample used in this study were morning shift engineering workers, while the duration of the study was carried out for 2 months starting from February-March 2025. Data analysis was carried out using the Miles and Huberman interactive model. Results: The results show that K3 practices have generally been implemented, but are still less than optimal, particularly in (1) inspection procedures which are hampered by delays and lack of communication and (2) compliance with the use of PPE. Meanwhile, CCV reporting was implemented effectively as evidenced by 408 reports recorded during the study period. Conclusion: The implementation of K3 at PT. PLN (Persero) ULP Kabupaten X has achieved a Zero Accident status, despite facing challenges such as a lack of discipline in the use of PPE due to size mismatches and delays in work permit approvals. The author recommends improving communication between management and field workers to improve compliance and safety performance as well as improving PPE procurement.